Implied volatility of options price based on black-scholes model using numerical method / Nor Azni Shahari ... [et al.] - Shahari, Nor Azni; A. Rahim, Nur Eliya Natasha; Ahmad, Aqilah; Suedan, Nur Aainaa Nadirah (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2022)
Price volatility is one of the most crucial factors for option pricing. The reason for the circumstances is because the option price is effortlessly affected by volatility changes. However, ideal market volatility forecasting is challenging, and despite the availabiIity of numerous models and methodologies, not all of them operate equally well for all stock markets. So, the ability to accurately assess price risks and make suitable investment decisions is useful for successful market trading that requires risk understanding, whether for pure speculation or to aid with hedging decisions (Ewing, 2010). There are two ways to determine the value of volatility of option prices, which are by historical volatility and implied volatility. Implied volatility (IV) is a metric used to forecast what the market thinks about the future price movements of an option's underlying stock. Although it can gradually change by a move higher or lower forvarious reasons, it can setthecurrent price of an existing option and helpsthe traders to discoverthe value of an option and compare it with others. Implied volatility works as a gauge of price risk for hedging and speculating choices since volatility of option price is a continually changing variable from time to time, so there must be a simple and fast approach to extract its value in the Black-Scholes model (BSM). Implied volatility can be determined by using an option pricing model and BSM is a widely used and well-known options pricing model. At an option- pricing formula, you'd see variables like current stock price, strike price, days until expiration, interest rates, dividends, and implied volatility, which are used to determine the option's price. Implied volatility is calculated by taking the market price of the option, entering it into the BSM formula, and back-solving for the value of the volatility.